Re‐exposure to morphine‐associated context facilitated long‐term potentiation in the vSUB‐NAc glutamatergic pathway via GluN2B‐containing receptor activation. (22nd December 2015) - Li, Yi‐Jing; Ping, Xing‐Jie; Qi, Chong; Shen, Fang; Sun, Lin‐Lin; Sun, Xiao‐Wei; Ge, Fei‐Fei; Xing, Guo‐Gang; Cui, Cai‐Lian
Abstract: The glutamatergic projection from the ventral subiculum of the hippocampus (vSUB) to the nucleus accumbens (NAc) shell has been reported to play a key role in drug‐related behavior. The GluN2B subunit of N‐methyl‐D‐aspartate receptors (NMDARs) in the NAc can be selectively elevated after the retrieval of drug‐conditioned memory. However, whether the increased GluN2B‐containing NMDARs (GluN2B‐NMDARs) are able to alter the synaptic plasticity of the vSUB‐NAc glutamatergic pathway remains unclear. Here, we found that the long‐term potentiation (LTP) in the vSUB‐NAc pathway was facilitated and the GluN2B subunit protein level was elevated in synaptoneurosomes of the NAc shell, but not in the core, following morphine‐induced conditioned place preference (CPP) expression in rats. The facilitated LTP was prevented by the GluN2B‐NMDAR antagonist RO25‐6981. Also, a neurochemical disconnection following microinjection of RO25‐6981 into the NAc shell, plus microinfusion of GABA agonist baclofen and muscimol into the contralateral vSUB prevented the expression of morphine‐induced CPP. These findings suggest that the retrieval of drug‐associated memory potentiated synaptic plasticity in the vSUB‐NAc pathway, which was dependent on GluN2B‐NMDAR activation in the NAc shell. These findings provide a new explanation for the mechanisms that underlie the morphine‐associated‐context memory. The GluN2B‐NMDARs may be regarded as a potential target for erasing morphine‐related memory. Abstract : Re‐exposure to the morphine‐associated context facilitated the long‐term potentiation induction in the vSUB‐nucleus accumbens (NAc) pathway. Intra‐NAc shell injection of GluN2B–N‐methyl‐d‐aspartate receptor antagonist RO25‐6981 prevented the long‐term potentiation facilitation. The inhibition of the GluN2B–N‐methyl‐d‐aspartate receptors in the vSUB‐NAc pathway prevented morphine conditioned place preference expression.